2015
DOI: 10.1038/npp.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial Memory Improvement after Gamma Ventral Capsulotomy in Treatment Refractory Obsessive–Compulsive Disorder Patients

Abstract: Gamma ventral capsulotomy (GVC) radiosurgery is intended to minimize side effects while maintaining the efficacy of traditional thermocoagulation techniques for the treatment of refractory obsessive-compulsive disorder (OCD). Neuropsychological outcomes are not clear based on previous studies and, therefore, we investigated the effects of GVC on cognitive and motor performance. A doubleblind, randomized controlled trial (RCT) was conducted with 16 refractory OCD patients allocated to active treatment (n = 8) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 49 publications
1
39
1
4
Order By: Relevance
“…Similar to our results, other studies have reported improved visuospatial memory. 33 Our results suggest that bilateral thermal lesioning of the ALIC with MRgFUS does not negatively affect various domains of neuropsychological function, including intelligence, memory, attention, learning ability and executive function. The positive effect on memory function may be explained by several mechanisms, such as amelioration of symptoms or interruption of abnormal circuits.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Similar to our results, other studies have reported improved visuospatial memory. 33 Our results suggest that bilateral thermal lesioning of the ALIC with MRgFUS does not negatively affect various domains of neuropsychological function, including intelligence, memory, attention, learning ability and executive function. The positive effect on memory function may be explained by several mechanisms, such as amelioration of symptoms or interruption of abnormal circuits.…”
Section: Discussionmentioning
confidence: 56%
“…The positive effect on memory function may be explained by several mechanisms, such as amelioration of symptoms or interruption of abnormal circuits. 33 However, improvements in Memory Quotient should be interpreted with caution, because they could have been due to learning effects through repeated examinations.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Up to the present time, only one randomized clinical trial and few case series have confirmed these encouraging results. 1,2,8,11,12,[14][15][16][17][18][25][26][27] The group from Charlottesville 27 believes that a bilateral single 4-mm isocenter delivering a maximum dose of 140-160 Gy is enough to show clinical improvement in patients with OCD, and reported a marked clinical improvement in 4 of 5 patients (80%) without any clinical side effects at a median follow-up duration of 24 months. The most recent study published by the group at the Karolinska Institute reported clinical results in 9 patients treated with single or double isocenters at higher doses (180-200 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…In the GKRS capsulotomy literature, only Lopes et al 1,17 and Rück et al 25 also analyzed secondary efficacy variables such as anxiety, depression, and GAF score at longterm follow-up. In the Brazilian series at 12 months, the active and sham groups did not differ statistically in terms of anxiety (Beck Anxiety Index, p = 0.46) and depression (BDI, p = 0.17).…”
Section: Table 2 Preoperative Value Last Follow-up Value and Percementioning
confidence: 99%
“…In these cases, Gamma ventral capsulotomy (GVC), a radiosurgical procedure which aims to create lesions in the ventral part of the anterior limb of the internal capsule (ALIC), has been used as a treatment option. Efficacy and safety of this procedure have been described in previous reports (6)(7)(8)(9), as well as neuropsychological outcomes (9)(10)(11). However, little research is devoted to the study of possible personality changes after GVC or similar neurosurgeries (12).…”
Section: Introductionmentioning
confidence: 91%